2016
DOI: 10.1200/jco.2016.34.3_suppl.130
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of physical function and falls among women with persistent symptoms of chemotherapy-induced peripheral neuropathy.

Abstract: 130 Background: Chemotherapy-induced peripheral neuropathy (CIPN) is a side effect of cancer treatment that may persist and impact physical function. Studies that quantify functional consequences associated with CIPN in post-treatment cancer survivors are rare, based on self-report, or use small samples. The purpose of this study was to compare objective and self-report measures of physical function, gait patterns, and falls between women cancer survivors with or without symptoms of CIPN. Methods: Baseline as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Our study assessed CIPN prevalence in a mean follow-up time of 5.6 years and found that 58.4% of patients reported persistent PN. This is consistent with a recent study of 462 women cancer survivors enrolled in an exercise trial in which 208 (45%) had CIPN symptoms an average of 6 years after treatment[18]. The data suggest the CIPN persists rather than resolving as expected for a substantial population of women with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study assessed CIPN prevalence in a mean follow-up time of 5.6 years and found that 58.4% of patients reported persistent PN. This is consistent with a recent study of 462 women cancer survivors enrolled in an exercise trial in which 208 (45%) had CIPN symptoms an average of 6 years after treatment[18]. The data suggest the CIPN persists rather than resolving as expected for a substantial population of women with breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In a recent exercise trial of women cancer survivors (n=462), the 208 (45%) women with CIPN symptoms experienced worse physical functioning, altered walking patterns, and more falls than women without CIPN symptoms[18]. Although these two studies differ in patient populations, with our study focusing on breast cancer survivors who have taken or are taking aromatase inhibitors enrolled in an ambulatory clinical care setting, whereas this study focused on breast cancer survivors participating in an exercise clinical trial with function assessments as its primary aim, the results are similar[18]. Our study found that moderate to severe CIPN not only doubled the fall rate, but could also be detrimental to aging breast cancer survivors’ quality of life and functional independence.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer survivors are at an increased risk of falling and the incidence of falling after chemotherapy is a concern for survivors’ long-term quality of life [19,31,12,10,8]. This study aims to provide clinicians with a more comprehensive understanding of the development of adverse effects associated with taxane therapy including the timing of symptom onset during taxane-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who undergo treatment with taxane drugs and/or develop CIPN often present with decreased postural stability [1318,11]. Recent research suggests that CIPN may also be associated with functional impairments during ambulation [19]. Isolated studies of the natural histories of patient-reported outcomes [20] and balance impairments [21] have previously been reported in breast cancer patients undergoing taxane-based chemotherapy; however, little is known about the development of gait impairments in this population or the concomitant development of these varied quality-of-life impairing adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…CIPN is associated with symptoms that include tingling, numbness, neuropathic pain and ataxia. More recently, in a cohort study of 462 women almost half of the patients continued to report symptoms of CIPN after an average of 5.8 years out from their diagnosis [ 2 ]. At this time there are limited treatment options for the treatment of CIPN and no treatment options for the prevention of CIPN [ 3 ].…”
Section: Introductionmentioning
confidence: 99%